Negative plate and lithium ion secondary battery
By using multi-layer coating technology and manufacturing recessed technology on the negative electrode of lithium-ion batteries, combined with hard carbon materials, the problem of taking into account both energy density and fast charging capabilities is solved, and high energy density and excellent fast charging performance are achieved.
Patent Information
- Application Number
- CN202411872295.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-18
AI Technical Summary
Existing lithium-ion batteries are difficult to take into account both the increase in energy density and the fast charging capacity. The thick electrodes lead to difficulty in infiltration of the electrolyte, the lithium ion transmission path increases, the lithium ion concentration gradient is too large, and the active substance at the bottom layer of the electrode cannot fully exert, resulting in the battery's fast charging capacity becoming worse.
The special structural design of the negative electrode sheet is adopted, and the manufacturing recessed portion technology is combined with the multi-layer coating technology. The negative electrode sheet includes a negative current collector and a negative electrode active material layer located on one side of the surface. The negative electrode active material layer is divided into multiple layers. The first coating is close to the negative electrode current collector, the second coating is away from the negative electrode current collector, the second coating contains hard carbon, and a recess is provided on the outer surface of the negative electrode active material layer.
Through this structural design, the lithium ion conduction capacity and capacity are improved, the battery's high energy density and excellent fast charging capabilities are achieved, and the battery's difficulties in taking into account both energy density and fast charging capabilities are solved.
Smart Images

Figure CN119650583A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and particularly to a negative electrode sheet and a lithium-ion secondary battery including the negative electrode sheet. Background Art
[0002] Lithium-ion batteries (LIBs) have great potential in electronic devices and electric vehicles. Current technologies are dedicated to improving the energy density and fast charging ability of the batteries.
[0003] For thick electrodes, the energy density of the battery can be improved to a certain extent, but it will make it difficult for the electrolyte to infiltrate, resulting in problems such as an increase in the lithium-ion transmission path, an excessive lithium-ion concentration gradient, and the inability of the active material at the bottom layer of the electrode to fully exert its function, thereby leading to a deterioration in the fast charging ability of the battery. The multi-layer composite electrode structure is a simple and efficient electrode structure design concept. The double-layer coating design in the prior art generally uses fast-charging graphite on the surface layer and high-capacity graphite at the bottom layer (the particle size of the high-capacity graphite is larger than that of the fast-charging graphite). However, in actual use, there are still problems that the energy density and fast charging ability cannot be兼顾.
[0004] Therefore, it is very important to improve the energy density and fast charging ability of the battery simultaneously. Summary of the Invention
[0005] The purpose of the present invention is to overcome the above problems existing in the prior art, and provide a negative electrode sheet and a lithium-ion secondary battery including the negative electrode sheet. The negative electrode sheet of the present invention has a special structure design, which combines the technology of manufacturing recesses with the multi-layer coating technology, so that the negative electrode sheet has excellent lithium-ion conduction ability and capacity utilization. The lithium-ion secondary battery (hereinafter simply referred to as the battery) including the negative electrode sheet of the present invention has a high energy density and fast charging ability.
[0006] In a first aspect of the present invention, a negative electrode sheet is provided. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector. The negative electrode active material layer includes a first coating and a second coating laminated along the thickness direction of the negative electrode sheet. The first coating is close to the negative electrode current collector, and the second coating faces away from the negative electrode current collector. The thickness of the negative electrode sheet is 30μm - 1000μm. The first coating includes a first negative electrode active material, and the second coating includes a second negative electrode active material. The second negative electrode active material includes a second graphite material and hard carbon. The ratio of the average particle size of the second negative electrode active material to the average particle size of the first negative electrode active material is L, and 1 < L ≤ 2.5. The outer surface of the negative electrode active material layer has recesses.
[0007] In the related art, the negative electrode sheet uses fast-charging graphite on the surface and high-capacity graphite on the bottom layer, which cannot effectively take into account both high energy density and fast charging capabilities. The inventors of the present invention have conducted a lot of research and found that the reasons for this problem are: first, the negative electrode active material located on the surface is subjected to greater force during rolling, resulting in a relatively low porosity of the surface layer, which makes the electrolyte wettability to the bottom layer negative electrode active material worse, resulting in a low overall battery capacity and poor fast charging capability. Second, the particle size of fast-charging graphite is smaller than that of high-capacity graphite, and the limit compaction of graphite particles with smaller particle sizes is also smaller; and during the rolling process, the graphite particles located on the surface are subjected to greater force than the graphite particles located on the bottom layer. Therefore, in order not to destroy the graphite particle structure of the surface layer as much as possible, the compaction density of the coating located at the bottom layer is low, which affects the energy density of the battery.
[0008] Based on the above reasons, the inventors of the present invention have conducted a large number of targeted experiments. It was found that: the negative electrode active material layer is divided into a multi-layer arrangement, so that the average particle size of the active material located on the relative surface layer is larger than the average particle size of the active material located on the relative bottom layer, and the ratio of the average particle sizes of the two is limited to a specific range. Such an arrangement can effectively improve the problem of incomplete capacity due to uneven force on the surface and bottom layers during the rolling process. In addition, hard carbon is a carbon material that is difficult to graphitize. Its internal crystal arrangement is disordered and the interlayer spacing is large (the interlayer spacing of hard carbon is ≥0.34nm). Therefore, it is more conducive to the embedding and extraction of lithium ions. It is precisely because of its special structure that the first coulombic efficiency and capacity of hard carbon are low. When hard carbon is included in the second negative electrode active material, the advantage of hard carbon for rapid extraction and extraction of lithium ions can be fully utilized.
[0009] The above arrangement can improve the battery's ability to balance high energy density and fast charging performance to a certain extent. Furthermore, a recess is provided on the outer surface of the negative electrode active material layer. The structure of the recess can increase the liquid storage space, improve the electrolyte infiltration into the negative electrode sheet (shorten the lithium insertion channel, reduce the tortuosity, and allow lithium ions to quickly pass through the surface layer to reach the inside of the negative electrode sheet), shorten the aging time, and solve the problems of low surface porosity and insufficient capacity of the underlying active material in the existing double-layer coating; at the same time, it can avoid the problem of lithium precipitation of the surface active material. Combining the three methods of multi-layer coating of the negative electrode sheet, using hard carbon materials in the coating located on the relative surface layer, and providing a recess on the outer surface of the negative electrode active material layer, can improve the lithium insertion ability of the active material with larger particle size on the surface layer and the active material with smaller particle size on the bottom layer, thereby improving the capacity; and can make up for the adverse effects of the disadvantages of hard carbon on the battery.
[0010] A second aspect of the present invention provides a lithium ion secondary battery, wherein the lithium ion secondary battery comprises the negative electrode sheet described in the first aspect of the present invention.
[0011] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0012] (1) The negative electrode sheet of the present invention has excellent lithium ion conductivity and capacity.
[0013] (2) The battery including the negative electrode sheet of the present invention has high energy density, excellent rate performance and cycle stability.
[0014] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The figure shows the distribution of the first coating layer and the second coating layer in one embodiment of the present invention.
[0016] Figure 2 Shown is a scanning electron microscope (SEM) image of the surface of the negative electrode sheet in an example of the present invention.
[0017] Figure 3 Shown is a SEM image of the surface of the negative electrode sheet in an example of the present invention.
[0018] Figure 4 FIG. 1 is a schematic diagram of the width of a slot in an example of the present invention; wherein, Figure 4 (a)- Figure 4 (c) The two long sides of the middle groove are straight lines. Figure 4 (d) The two long sides of the middle groove are curved lines.
[0019] Figure 5 FIG. 1 is a schematic diagram of the spacing of the grooves in an example of the present invention; wherein, Figure 5 (a) is the case where two adjacent long sides are straight and parallel. Figure 5 (b) is the case where two adjacent long sides are straight lines and not parallel. Figure 5 (c) is the case where two adjacent long sides are curved lines.
[0020] Figure 6 FIG. 1 is a schematic cross-sectional view of a concave portion in an example of the present invention; wherein, Figure 6 The recesses in (a)-6(f) have different depths. DETAILED DESCRIPTION
[0021] The following provides a detailed description of the specific embodiments of the present invention. It should be understood that the specific embodiments described herein are only for explaining and understanding the present invention, and are not used to limit the present invention.
[0022] In the first aspect of the present invention, a negative electrode sheet is provided. The negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector. The negative electrode active material layer may include a first coating layer and a second coating layer stacked along the thickness direction of the negative electrode sheet. Among them, the first coating layer is close to the negative electrode current collector, and the second coating layer faces away from the negative electrode current collector. As Figure 1 Shown is a schematic diagram of the distribution of the first coating layer and the second coating layer in an example of the present invention. As can be seen from the figure, the negative electrode sheet includes a negative electrode current collector 1 and a negative electrode active material layer 2 located on one surface of the negative electrode current collector 1; the negative electrode active material layer 2 includes a first coating layer 21 and a second coating layer 22 stacked along the thickness direction of the negative electrode sheet. The first coating layer 21 is close to the negative electrode current collector 1, and the second coating layer 22 faces away from the negative electrode current collector 1. It should be noted that Figure 1 only the case of setting the negative electrode active material layer on one side is given, and the negative electrode active material layer may also be located on both surfaces of the negative electrode current collector.
[0023] In the present invention, the thickness of the negative electrode sheet may be 30 μm - 1000 μm, such as 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm or 1000 μm.
[0024] In one example, the thickness of the negative electrode sheet is 70 μm - 210 μm.
[0025] In the present invention, the first coating layer may include a first negative electrode active material, and the second coating layer may include a second negative electrode active material. The second negative electrode active material may include a second graphite material and hard carbon. The ratio of the average particle size of the second negative electrode active material to the average particle size of the first negative electrode active material is L, 1 < L ≤ 2.5, and L is, for example, 1.01, 1.05, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4 or 2.5.
[0026] In one example, 1.05 ≤ L ≤ 1.4.
[0027] In the present invention, the outer surface of the negative electrode active material layer may have a concave portion.
[0028] The inventors of the present invention have found that if the relationship between the ratio L of the average particle size of the second negative electrode active material to the first negative electrode active material and the depth of the recess is further regulated, the ability of the battery to balance high energy density and fast charging performance can be further improved. The reason is that the average particle size of the second negative electrode active material located at the relative surface layer is greater than the average particle size of the second negative electrode active material located at the relative bottom layer, and the ratio of the two can reflect the difference in particle size. Within a certain range, the larger the ratio of the two, the larger the difference in particle size, the smaller the overall compaction density of the negative electrode sheet, and the more conducive to the fast charging performance of the battery, but the thicker the battery, the lower the volume energy density; at this time, the depth of the recess does not need to be too deep. Because the greater the depth of the recess, the more active material mass is lost, which is not conducive to improving the energy density of the battery. The smaller the ratio of the two, the smaller the difference in particle size, the larger the overall compaction density of the negative electrode sheet, and the more conducive to improving the energy density of the battery, but the fast charging performance will deteriorate accordingly. At this time, a deeper recess depth is required to improve the infiltration of the electrolyte into the bottom negative electrode sheet. Therefore, by further regulating the relationship between L and the depth of the recess, the performance of the underlying and surface negative electrode active materials can be fully utilized within a specific range, thereby improving the battery capacity and fast charging capability, and making the battery have high energy density and excellent rate performance.
[0029] In the present invention, the depth of the concave portion is h, in μm. L and h may satisfy: 6≤L×h≤300, where L×h is, for example, 6, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 200 or 300.
[0030] In one example, 14≤L×h≤100.
[0031] In one example, 16≤L×h≤86.
[0032] In the present invention, the average particle size of the first negative electrode active material may be 5 μm-15 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm. The average particle size of the second negative electrode active material may be 9 μm-24 μm, for example, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm or 24 μm.
[0033] In the present invention, the average particle size of the first negative electrode active material and the average particle size of the second negative electrode active material can be obtained by testing by conventional methods in the art, for example, using an argon ion milling apparatus to cut the negative electrode sheet along the thickness direction, and then using a scanning electron microscope (SEM) to obtain a cross-sectional mirror image of the negative electrode sheet along the thickness direction, and randomly selecting at least 20 first negative electrode active material particles and 20 second negative electrode active material particles in the field of view of the mirror image, measuring the particle sizes respectively, and taking the average values, the average particle size of the first negative electrode active material and the average particle size of the second negative electrode active material can be obtained.
[0034] In the present invention, the porosity of the second coating layer is greater than the porosity of the first coating layer.
[0035] In the present invention, the ratio of the porosity of the first coating layer to the porosity of the second coating layer may be 0.5-0.98, for example, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or 0.98.
[0036] In one example, the ratio of the porosity of the first coating layer to the porosity of the second coating layer is 0.7-0.9.
[0037] The porosity of the negative electrode active material layer can reflect the wettability of the electrolyte to the negative electrode sheet as a whole to a certain extent. The porosity of the second coating layer is greater than that of the first coating layer, which can make the porosity in the negative electrode sheet have a certain gradient, which is conducive to the infiltration of the electrolyte. And when the ratio of the two is within a specific range, the porosity gradient formed can form a driving force to promote the infiltration of the electrolyte into the first coating layer located at the relatively bottom layer, thereby improving the overall capacity of the battery and the fast charging performance.
[0038] In the present invention, the porosity of the first coating layer may be 10%-40%, for example, 10%, 15%, 20%, 25%, 30%, 35% or 40%. The porosity of the second coating layer may be 20%-50%, for example, 20%, 25%, 30%, 35%, 40%, 45% or 50%.
[0039] In one example, the porosity of the first coating layer is 20%-25%, and the porosity of the second coating layer is 25%-35%.
[0040] In the present invention, the porosity of the first coating and the porosity of the second coating can be tested by conventional methods in the art, such as using laser scanning technology, scanning the cross-section of the first coating and the second coating along the thickness direction by a laser beam to obtain the cross-sectional morphology information of the first coating and the second coating, reconstructing the pore structure inside the coating by a reverse engineering method, and calculating the porosity.
[0041] In the present invention, the first negative electrode active material may include a first graphite material.
[0042] In the present invention, the OI value of the second graphite material is greater than the OI value of the first graphite material.
[0043] The OI value of graphite material is used to describe the order of its interlayer arrangement, which can reflect the orientation of the crystal structure of graphite material and has a great influence on the electrochemical performance of negative electrode active material. When the OI value of the second graphite material is greater than the OI value of the first graphite material, it means that the capacity of the negative electrode active material located at the relatively surface layer is higher, which is conducive to the use of capacity. The OI value of the first graphite material is smaller, which means that the negative electrode active material located at the relatively bottom layer is more conducive to the diffusion of lithium ions, which helps to improve the rate performance of the battery while maintaining a higher energy density.
[0044] In the present invention, the OI value of the first graphite material may be 9-24, for example, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 or 24. The OI value of the second graphite material may be 12-26, for example, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 or 26.
[0045] In the present invention, the OI value of the first graphite material and the OI value of the second graphite material can be measured and obtained by conventional methods in the art, such as using an X-ray diffractometer (XRD).
[0046] In the present invention, the specific capacity of the second graphite material is greater than the specific capacity of the first graphite material. When the specific capacity of the second graphite material is greater than the specific capacity of the first graphite material, the energy density of the battery can be improved without affecting the fast charging performance of the battery.
[0047] In the present invention, the specific capacity of the first graphite material may be 320mAh / g-360mAh / g, such as 320mAh / g, 330mAh / g, 340mAh / g, 350mAh / g or 360mAh / g. The specific capacity of the second graphite material may be 340mAh / g-370mAh / g, such as 340mAh / g, 350mAh / g, 360mAh / g or 370mAh / g.
[0048] In the present invention, the specific capacity of the first graphite material and the specific capacity of the second graphite material can be obtained by testing by conventional methods in the art, for example, the first graphite material or the second graphite material is used as a working electrode, and a lithium sheet is used as a reference electrode to assemble a half-cell, and the above-mentioned half-cell curve is obtained by testing using an electrochemical workstation, that is, the standard potential curve of the first graphite material or the second graphite material relative to the lithium sheet, and the specific capacity = capacitance (unit mAh) / mass of the first graphite material (or the second graphite material) (unit g).
[0049] In the present invention, the specific surface area of the first negative electrode active material is greater than the specific surface area of the second negative electrode active material. The specific surface area of the first negative electrode active material may be 1.2 m 2 / g-4m 2 / g, for example, 1.2m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g or 4m 2 / g. The specific surface area of the second negative electrode active material can be 1m 2 / g-3.5m 2 / g, for example, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g or 3.5m 2 / g.
[0050] In the present invention, the specific surface area of the first negative electrode active material and the specific surface area of the second negative electrode active material can be measured by a conventional method in the art, such as the BET (Brunauer-Emmett-Teller) method.
[0051] In the present invention, the tap density of the second coating is greater than the tap density of the first coating. The tap density of the first coating may be 0.6 g / cm 3 -0.85g / cm 3 , for example 0.6 g / cm 3 , 0.65g / cm 3 , 0.7g / cm 3 , 0.75g / cm 3 , 0.8g / cm 3 or 0.85g / cm 3 The tap density of the second coating layer may be 0.7 g / cm 3-1g / cm 3 , for example 0.7 g / cm 3 , 0.75g / cm 3 , 0.8g / cm 3 , 0.85g / cm 3 , 0.9g / cm 3 , 0.95g / cm 3 or 1g / cm 3 .
[0052] In the present invention, the tap density of the first coating layer and the tap density of the second coating layer can be measured by conventional methods in the art, such as using a tap density meter.
[0053] In the present invention, the compaction density of the second coating is greater than the compaction density of the first coating. The compaction density of the first coating may be 1.4 g / cm 3 -1.8g / cm 3 , for example 1.4 g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 or 1.8 g / cm 3 The compacted density of the second coating layer may be 1.5 g / cm 3 -2g / cm 3 , for example 1.5 g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 or 2g / cm 3 .
[0054] In the present invention, the thickness of the first coating layer may be 10 μm-80 μm, for example, 10 μm, 15 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm or 80 μm. The thickness of the second coating layer may be 20 μm-150 μm, for example, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm.
[0055] In the present invention, the thickness of the first coating layer and the thickness of the second coating layer refer to the first coating layer thickness and the second coating layer thickness on a single side of the negative electrode current collector.
[0056] In the present invention, the surface density of the second coating is greater than or equal to the surface density of the first coating. The surface density of the first coating is 2 mg / cm 2 -15mg / cm 2 , for example 2 mg / cm 2 、3mg / cm 2 , 4mg / cm 2 , 5mg / cm 2 , 6mg / cm 2 , 7mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 、10mg / cm 2 、11mg / cm 2 , 12mg / cm 2 、13mg / cm 2 、14mg / cm 2 or 15mg / cm 2 The surface density of the second coating is 4 mg / cm 2 -20mg / cm 2 , for example 4 mg / cm 2 , 5mg / cm 2 , 6mg / cm 2 , 7mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 、10mg / cm 2 、11mg / cm 2 , 12mg / cm 2 、13mg / cm 2 、14mg / cm 2 、15mg / cm 2 、16mg / cm 2 、17mg / cm 2 、18mg / cm 2 、19mg / cm 2 or 20mg / cm 2 .
[0057] In the present invention, the recess may include a hole and / or a groove. When the recess is a hole, the number of the recess (i.e., the hole) is greater than or equal to 2. When the recess is a groove, the number of the recess (i.e., the groove) is greater than or equal to 1.
[0058] In one embodiment, the recessed portion includes a hole. The shape of the positive projection of the hole on the surface of the negative electrode sheet can be a regular pattern or an irregular pattern. Figure 2The figure shows a SEM image of the surface of the negative electrode sheet in an example of the present invention. It can be seen from the figure that the surface of the negative electrode sheet has a plurality of holes (ie, the outer surface of the negative electrode active material layer has a plurality of holes).
[0059] In the present invention, the pore size may be 40 μm-200 μm, for example, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm.
[0060] In the present invention, the aperture of the hole has the conventional meaning in the art. When the shape of the orthographic projection of the hole on the surface of the negative electrode sheet is a "regular circle", the aperture of the hole is the diameter of the regular circle; when the shape of the orthographic projection of the hole on the surface of the negative electrode sheet is a non-"regular circle" (such as an ellipse or an irregular curved polygon), the aperture of the hole is the diameter of an equivalent circle with the same area as the non-"regular circle". The "aperture of the hole" can be obtained by conventional means in the art, such as by SEM, selecting all or at least 10 holes in the electron microscope field of view, measuring the aperture, and taking the average value.
[0061] In the present invention, the spacing between the holes can be 50μm-1mm, for example, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 200μm, 300μm, 400μm, 500μm, 600μm, 700μm, 800μm, 900μm or 1mm.
[0062] In one example, the pitch of the holes is 100 μm-300 μm.
[0063] In the present invention, the spacing between the holes has the conventional meaning in the art, and refers to the shortest distance between the edges of two adjacent holes on the surface of the negative electrode sheet. The "spacing between the holes" can be tested by conventional means in the art, for example, by SEM, selecting all or at least 10 groups of adjacent holes in the field of view of the electron microscope, measuring the spacing, and taking the average value.
[0064] In one embodiment, the recessed portion includes a groove. The projection of the groove on the surface of the negative electrode sheet may be a regular pattern or an irregular pattern. Figure 3 The figure shows a SEM image of the surface of the negative electrode sheet in an example of the present invention. It can be seen from the figure that the surface of the negative electrode sheet has a plurality of grooves (ie, the outer surface of the negative electrode active material layer has a plurality of grooves).
[0065] In the present invention, the width of the groove may be 20 μm-150 μm, for example, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm.
[0066] In one example, the width of the groove is 60 μm-120 μm.
[0067] In the present invention, the width of the groove has the conventional meaning in the art. The projection of the groove on the surface of the negative electrode sheet includes two long sides, and the width of the groove refers to the average distance from one long side to the other long side in the length direction or width direction of the negative electrode sheet. Figure 4 FIG. 1 is a schematic diagram of the width of a slot in an example of the present invention; wherein, Figure 4 (a)- Figure 4 (c) The two long sides of the middle groove are straight lines. Figure 4 (d) The two long sides of the groove are curved. Figure 4 (a) and Figure 4 In (b), the two long sides are arranged in parallel, so the vertical distance from any point on one long side to the other long side in the width direction of the negative electrode sheet is equal. In this case, the width of the slot is the vertical distance d from any point on one long side to the other long side in the length direction or width direction of the negative electrode sheet. Figure 4 In (c), the two long sides of the slot are straight lines, but they are not parallel. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the width of the slot can be averaged, that is, on one long side, based on the length of the side, 50 points are selected at equal distances (that is, the distance between each point is equal, so that the selection of points can make the calculation result more accurate), and the width d corresponding to each point is measured, and the average value is taken to get the width of the slot. Figure 4 In (d), the two long sides are curved. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the width of the slot can also be averaged, that is, 50 points are randomly selected on one long side (due to Figure 4 In (d), the two long sides are curved and do not exist. Figure 4 (c) The relationship between the two long sides, therefore, 50 points can be randomly selected for measurement), the width d corresponding to each point is measured, and the average value is taken to obtain the width of the groove. The "groove width" can be tested by conventional means in the art, for example, by SEM, all or at least 5 grooves are selected in the electron microscope field, the width is measured, and the average value is taken.
[0068] In the present invention, the spacing of the grooves may be 200 μm-3 mm, for example, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1 mm, 2 mm or 3 mm.
[0069] In one example, the spacing of the grooves is 0.8 mm-2 mm.
[0070] It is understandable that when there is only one groove on the surface of the negative electrode sheet, there is no spacing between the grooves.
[0071] In the present invention, the spacing of the grooves has the conventional meaning in the art, and refers to the average distance between two adjacent long sides of two adjacent grooves in the length direction or width direction of the negative electrode sheet. Figure 5 FIG. 1 is a schematic diagram of the spacing of the grooves in an example of the present invention; wherein, Figure 5 (a) is the case where two adjacent long sides are straight and parallel. Figure 5 (b) is the case where two adjacent long sides are straight lines and not parallel. Figure 5 (c) is the case where two adjacent long sides are curved. Figure 5 In (a), the two adjacent long sides are straight and parallel, so in the width direction, the distance from any point on one long side to the other long side is equal. In this case, the spacing of the grooves is the distance D from any point on one long side to the other long side in the width direction. Figure 5 In (b), the two adjacent long sides are straight lines, but they are not parallel. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the spacing of the slots can be averaged, that is, on one long side, based on the length of the side, 50 points are selected at equal distances (that is, the distance between each point is equal, so that the selection of points can make the calculation result more accurate), and the width D corresponding to each point is measured, and the average value is taken to get the spacing. Figure 5 In (c), the two adjacent long sides are curved. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the spacing of the grooves can also be averaged, that is, 50 points are randomly selected on one long side (due to Figure 5 (c) The two long sides are curved, so there is no Figure 5 (b) The relationship between the two long sides, therefore, 50 points can be randomly selected for measurement), the width D corresponding to each point is measured, and the average value is taken to obtain the spacing. The "slot spacing" can be obtained by conventional means in the art, such as by SEM, selecting all or at least 5 groups of adjacent slots in the electron microscope field, measuring the spacing, and taking the average value.
[0072] By adjusting the size of the recess, the wetting effect of the electrolyte on the negative electrode sheet can be further improved, which is beneficial to capacity utilization and charge and discharge efficiency.
[0073] In the present invention, the depth h of the recess can be 5-250, in μm, for example, 5μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, 200μm, 210μm, 220μm, 230μm, 240μm or 250μm.
[0074] In one example, the depth h of the concave portion is 10-70, in μm.
[0075] In one example, the depth h of the concave portion is 10-25, in μm.
[0076] In one example, the depth h of the concave portion is 20-45, in μm.
[0077] In one example, the depth h of the concave portion is 40-75 μm.
[0078] It can be understood that for a wound battery, the negative electrode sheet will have a single-sided area and a double-sided area (the single-sided area refers to: in this area, only one side of the negative electrode collector has a negative electrode active material layer; the double-sided area refers to: in this area, both sides of the negative electrode collector have a negative electrode active material layer).
[0079] In the present invention, the depth h of the concave portion refers to the maximum value of the vertical distance from any point in the concave portion (located in the double-sided area) to the outer surface of the negative electrode sheet. The depth h of the concave portion can be measured by conventional means in the art, such as by a 3D profilometer or SEM, selecting all or at least 10 concave portions, measuring the depth of each concave portion, and taking the average value.
[0080] In the present invention, if Figure 6 FIG. 1 is a schematic cross-sectional view of a concave portion in an example of the present invention; wherein, Figure 6 The concave portions in (a)-6(f) have different depths. As can be seen from the figure, the outer surface of the negative electrode active material layer 2 has a concave portion 3. Figure 6 In (a), the recess 3 is located in the second coating 22 (ie, the recess 3 does not penetrate the second coating 22); Figure 6 In (b), the recess 3 is located in the first coating 21 and the second coating 22 (ie, the recess 3 penetrates the second coating 22 but does not penetrate the first coating 21); Figure 6In (c), the recess 3 penetrates the first coating 21 and the second coating 22 on one side of the negative electrode current collector 1 and passes through a portion of the negative electrode current collector 1; Figure 6 In (d), the recess 3 penetrates the negative electrode current collector 1 from one side of the negative electrode sheet and passes through part of the first coating 21 on the other side; Figure 6 In (e), the recess 3 penetrates the negative electrode current collector 1 from one side of the negative electrode sheet, penetrates the first coating 21 on the other side, and passes through part of the second coating 22; Figure 6 In (f), the recess 3 penetrates the negative electrode sheet.
[0081] In the present invention, the shape of the cross section of the recessed portion along the thickness direction of the negative electrode sheet is not limited, and may be a rectangle or a cone.
[0082] In the present invention, the negative electrode current collector may have a region having a negative electrode active material layer on only one side of the surface (i.e., the single-sided region described above), and the ratio of the depth of the recessed portion on the outer surface of the negative electrode active material layer located in the region to the thickness of the negative electrode active material layer may be 0.33-0.5, for example, 0.33, 0.35, 0.4, 0.45 or 0.5.
[0083] The area where the negative electrode current collector has a negative electrode active material layer on only one side of the surface is a single-sided area. When the ratio of the depth of the recessed portion on the outer surface of the negative electrode active material layer located in the single-sided area to the thickness of the negative electrode active material layer is within a specific range, the structural stability of the negative electrode sheet is higher and the adhesion between the negative electrode active material layer and the negative electrode current collector is stronger.
[0084] In one example, both sides of the negative electrode sheet have the recessed portions. The positions of the recessed portions located on both sides of the negative electrode sheet can be offset from each other or can overlap with each other.
[0085] In the present invention, the first graphite material and the second graphite material may each independently include artificial graphite and / or natural graphite.
[0086] In the present invention, the first negative electrode active material may also include at least one of hard carbon, soft carbon, mesophase carbon microspheres, soft carbon-coated graphite materials, and hard carbon-coated graphite materials. The second negative electrode active material may also include at least one of soft carbon, mesophase carbon microspheres, soft carbon-coated graphite materials, and hard carbon-coated graphite materials.
[0087] In one example, the mass content of hard carbon in the second negative electrode active material is greater than the mass content of hard carbon in the first negative electrode active material. As mentioned above, hard carbon is conducive to the embedding and extraction of lithium ions, but its initial coulombic efficiency and capacity are low. By regulating and making the mass content of hard carbon in the second negative electrode active material greater than the mass content of hard carbon in the first negative electrode active material, the advantage of hard carbon in facilitating the embedding and extraction of lithium ions can be further fully utilized, and the insufficiency of the initial coulombic efficiency and capacity of hard carbon can be compensated.
[0088] In the present invention, the average particle size of the hard carbon can be 3μm-20μm, for example, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm.
[0089] In the present invention, based on the total mass of the first negative electrode active material, the content of hard carbon is ≤6%, for example, 0.5%, 1%, 2%, 3%, 4%, 5% or 6%. Based on the total mass of the second negative electrode active material, the content of hard carbon can be 2%-10%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0090] In one example, based on the total mass of the first negative electrode active material, the content of hard carbon is ≤3%. Based on the total mass of the second negative electrode active material, the content of hard carbon is 3%-6%.
[0091] In the present invention, the first coating layer and the second coating layer may also independently include a negative electrode conductive agent, which includes at least one of conductive carbon black, conductive graphite, carbon nanotubes (including multi-walled carbon nanotubes and / or single-walled nanotubes) and graphene.
[0092] In the present invention, the first negative electrode active material and the second negative electrode active material may also independently include a silicon-based material. The silicon-based material may include at least one of elemental silicon, silicon-carbon material, silicon-oxygen material and silicon alloy. The silicon-carbon material refers to a composite material including elemental silicon and elemental carbon. The silicon-oxygen material refers to a composite material including elemental silicon and elemental oxygen.
[0093] In the present invention, the mass content of silicon in the second negative electrode active material is greater than the mass content of silicon in the first negative electrode active material. When the mass content of silicon in the second negative electrode active material is greater than the mass content of silicon in the first negative electrode active material, it is beneficial to the cycle stability of the battery. This is because silicon-based materials have a large volume expansion / contraction during the battery charge and discharge cycle, and when more silicon-based materials are located on the surface of the negative electrode sheet, part of the volume expansion of the silicon-based material can be converted into expansion inside the negative electrode sheet; and the outer surface of the negative electrode active material layer has a concave portion, and the second negative electrode active material includes hard carbon; the setting of the concave portion is beneficial to provide a certain buffer space for the expansion of the silicon-based material matrix, and the hard carbon is beneficial to the embedding and extraction of lithium ions, which can alleviate the embedding and extraction of lithium ions in the silicon-based material, making the silicon-based material more uniform and gentle in the extraction of lithium. At this time, the thickness expansion rate of the negative electrode sheet is small, and the deformation rate of the battery is low, which is beneficial to the cycle stability.
[0094] In the present invention, the mass content of silicon in the first negative electrode active material may be 1%-30%, for example, 1%, 5%, 10%, 15%, 20%, 25% or 30%. The mass content of silicon in the second negative electrode active material may be 2%-50%, for example, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%.
[0095] In one example, the mass content of silicon in the first negative electrode active material is 2%-10%, and the mass content of silicon in the second negative electrode active material is 5%-15%.
[0096] In one example, the silicon-based material includes the silicon-carbon material. The particle size distribution of the silicon-carbon material can be Dv10 of 3μm-6μm (for example, 3μm, 4μm, 5μm or 6μm), Dv50 of 6μm-12μm (for example, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm or 12μm), and Dv90 of 12μm-25μm (for example, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm or 25μm).
[0097] In the present invention, the particle size distribution Dv10, Dv50 and Dv90 of the silicon-carbon material can be measured by conventional methods in the art, such as a laser particle size analyzer.
[0098] In the present invention, the negative electrode current collector may include a metal layer and a carbon coating layer located on at least one side of the metal layer. The carbon coating layer may include at least one of conductive carbon black, conductive graphite, carbon nanotubes and graphene.
[0099] A second aspect of the present invention provides a lithium ion secondary battery, which may include the negative electrode sheet described in the first aspect of the present invention.
[0100] In the present invention, after 20 cycles of the lithium ion secondary battery, the elongation of the negative electrode collector in the first direction can be 0.5%-15%, for example, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%; wherein the cycle conditions are: at 25°C±2°C, stand for 5 minutes, discharge at 0.2C to 3.0V, stand for 5 minutes, charge at 0.7C to 4.53V, cut off at 0.025C, stand for 5 minutes, discharge at 0.2C to 3.0V, stand for 5 minutes, and cycle at 3.5C for 20 weeks. After 20 cycles of the lithium ion secondary battery, the tensile strength of the negative electrode collector can be 200MPa-1000MPa, for example, 300MPa, 400MPa, 500MPa, 600MPa, 700MPa, 800MPa, 900MPa or 1000MPa; wherein the cycle conditions are: at 25°C±2°C, standing for 5min, discharging at 0.2C to 3.0V, standing for 5min, charging at 0.7C to 4.53V, cutting off at 0.025C, standing for 5min, discharging at 0.2C to 3.0V, standing for 5min, and cycling at 3.5C for 20 weeks.
[0101] In one example, after the lithium-ion secondary battery has been cycled for 20 cycles, the tensile strength of the negative electrode current collector is 300 MPa-700 MPa.
[0102] By controlling the elongation and tensile strength of the negative electrode current collector, the energy density and cycle stability of the battery can be further improved, especially when the negative electrode active material includes silicon-based materials. A negative electrode current collector with a specific elongation and tensile strength means that it can not only better adapt to different shapes and sizes during battery manufacturing to reduce material damage caused by mechanical stress during battery assembly or volume expansion of active materials (especially silicon-based materials) during battery cycling. It can also withstand greater stress without breaking when the battery is subjected to external force, which is crucial to maintaining the structural stability and cycle stability of the battery.
[0103] In the present invention, the first direction refers to a direction perpendicular to the extension direction of the negative electrode tab, and is also the length direction of the negative electrode sheet.
[0104] In the present invention, the lithium-ion secondary battery may further include a positive electrode sheet, the positive electrode sheet may include a positive electrode current collector, and the positive electrode current collector may include aluminum foil and / or carbon-coated aluminum foil.
[0105] In the present invention, after 20 cycles of the lithium ion secondary battery, the elongation of the positive electrode collector in the first direction can be 0.5%-5%, for example, 0.5%, 1%, 2%, 3%, 4% or 5%; wherein the cycle conditions are: at 25°C±2°C, stand for 5 minutes, discharge at 0.2C to 3.0V, stand for 5 minutes, charge at 0.7C to 4.53V, cut off at 0.025C, stand for 5 minutes, discharge at 0.2C to 3.0V, stand for 5 minutes, and cycle at 3.5C for 20 weeks. After 20 cycles of the lithium ion secondary battery, the tensile strength of the positive electrode current collector can be 100 MPa-400 MPa, for example, 100 MPa, 200 MPa, 300 MPa or 400 MPa; wherein the cycle conditions are: at 25°C±2°C, stand for 5 min, discharge at 0.2C to 3.0 V, stand for 5 min, charge at 0.7C to 4.53 V, cut off at 0.025C, stand for 5 min, discharge at 0.2C to 3.0 V, stand for 5 min, and cycle at 3.5C for 20 weeks.
[0106] In one example, after the lithium-ion secondary battery has been cycled for 20 cycles, the tensile strength of the positive electrode current collector is 100 MPa-250 MPa.
[0107] In the present invention, the negative electrode sheet may have a lug-center structure and / or a multi-lug structure. The positive electrode sheet may have a lug-center structure and / or a multi-lug structure.
[0108] In the present invention, the components of the battery other than the positive electrode sheet and the negative electrode sheet (such as a separator and an electrolyte) can be conventionally selected in the art.
[0109] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent a difference in order.
[0110] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0111] In the following examples, unless otherwise specified, all materials used were commercially available of analytical grade.
[0112] The following examples are used to illustrate the lithium ion secondary battery of the present invention.
[0113] Example 1
[0114] Prepare the battery as follows:
[0115] (1) Preparation of negative electrode sheet
[0116] The first negative electrode active material (average particle size of 8.5 μm, specific surface area of 3.6 m 2 / g; including artificial graphite and silicon-carbon material, wherein the mass ratio of artificial graphite to silicon-carbon material is 98:2; the OI value of artificial graphite is 10, the specific capacity is 352mAh / g; the mass content of silicon in the silicon-carbon material is about 60%), styrene-butadiene rubber and conductive carbon black are mixed in a mass ratio of 95:3:2, deionized water is added to prepare a first coating slurry; the second negative electrode active material (average particle size of 9μm, specific surface area of 3.4m 2 / g; including artificial graphite, hard carbon and silicon-carbon material, wherein the mass ratio of artificial graphite, hard carbon and silicon-carbon material is 89:6:5, the OI value of artificial graphite is 12, and the specific capacity is 354mAh / g; the mass content of silicon in the silicon-carbon material is about 60%, and the average particle size of hard carbon is 10μm), styrene-butadiene rubber and conductive carbon black are mixed evenly according to the mass ratio of 95:3:2, and deionized water is added to prepare a second coating slurry; the first coating slurry and the second coating slurry are coated on the surface of the carbon-coated copper foil by a transfer coater, and after drying and roller pressing, grooves are made on the surface (the depth h of the groove is 31μm, the width is 82μm, and the spacing is 1.2mm) to obtain a negative electrode sheet;
[0117] Wherein, the ratio L of the average particle size of the second negative electrode active material to the average particle size of the first negative electrode active material is 1.059; L×h is 32.8;
[0118] The porosity of the first coating layer is 20.3%, the porosity of the second coating layer is 29.2%, and the ratio of the porosity of the first coating layer to the porosity of the second coating layer is 0.7;
[0119] The surface density of the first coating is 7.24 mg / cm 2 The surface density of the second coating is 7.24 mg / cm 2 ;
[0120] The thickness of the first coating layer is 24 μm, the thickness of the second coating layer is 30 μm, and the total thickness of the negative electrode sheet is 114 μm;
[0121] The ratio of the depth of the groove on the outer surface of the negative electrode active material layer located in the single-sided area to the thickness of the negative electrode active material layer satisfies 0.33-0.5;
[0122] The mass content of silicon in the first negative electrode active material is 1.2%, and the mass content of silicon in the second negative electrode active material is 3%.
[0123] (2) Preparation of positive electrode
[0124] Lithium cobalt oxide, polyvinylidene fluoride and conductive carbon black were mixed in a mass ratio of 97.5:1.5:1, and N-methylpyrrolidone (NMP) was added to prepare a positive electrode active material slurry. The positive electrode active material slurry was evenly coated on the surface of the carbon-coated aluminum foil, dried, and compacted by a roller press to obtain a positive electrode sheet.
[0125] (3) Preparation of electrolyte
[0126] In a glove box filled with argon (H 2 O<0.1ppm,O 2 <0.1ppm), ethylene carbonate, dimethyl carbonate and 1,2-propylene glycol carbonate were mixed in a volume ratio of 1:1:1, 1M lithium hexafluorophosphate was added, and stirred evenly. After the water content and free acid were tested to be qualified, an electrolyte was obtained.
[0127] (4) Preparation of batteries
[0128] The negative electrode sheet prepared in step (2), the separator (the two sides of the polyethylene substrate are respectively a boehmite ceramic layer and a polyvinylidene fluoride adhesive layer) and the negative electrode sheet prepared in step (1) are wound to form a winding core, and the aluminum pole ear and the copper-plated nickel pole ear are welded after hot pressing; after liquid injection, the battery is formed, sorted, and OCV tested to obtain a battery, wherein both the positive electrode sheet and the negative electrode sheet have a central pole ear structure.
[0129] Example 2
[0130] The same method as in Example 1 is used, except that the negative electrode sheet is prepared in step (1), specifically as follows:
[0131] The first negative electrode active material (average particle size of 10 μm, specific surface area of 3 m 2 / g; including artificial graphite, hard carbon and silicon-carbon materials, wherein the mass ratio of artificial graphite, hard carbon and silicon-carbon materials is 94:1:5; the OI value of artificial graphite is 16, the specific capacity is 354mAh / g; the mass content of silicon in the silicon-carbon material is about 60%), styrene-butadiene rubber and conductive carbon black are mixed in a mass ratio of 95:3:2, deionized water is added to prepare a first coating slurry; the second negative electrode active material (average particle size of 12μm, specific surface area of 2.7m 2 / g; including artificial graphite, hard carbon and silicon-carbon material, wherein the mass ratio of artificial graphite, hard carbon and silicon-carbon material is 87:3:10, the OI value of artificial graphite is 20, and the specific capacity is 355mAh / g; the mass content of silicon in the silicon-carbon material is about 60%, and the average particle size of hard carbon is 10μm), styrene-butadiene rubber and conductive carbon black are mixed evenly according to the mass ratio of 95:3:2, and deionized water is added to prepare a second coating slurry; the first coating slurry and the second coating slurry are coated on the surface of the carbon-coated copper foil by a transfer coater, and after drying and roller pressing, grooves are made on the surface (the depth h of the groove is 43μm, the width is 96μm, and the spacing is 1.5mm) to obtain a negative electrode sheet;
[0132] Wherein, the ratio L of the average particle size of the second negative electrode active material to the average particle size of the first negative electrode active material is 1.2; L×h is 51.6;
[0133] The porosity of the first coating layer is 22.4%, the porosity of the second coating layer is 25%, and the ratio of the porosity of the first coating layer to the porosity of the second coating layer is 0.9;
[0134] The surface density of the first coating is 7.24 mg / cm 2 The surface density of the second coating is 7.38 mg / cm 2 ;
[0135] The thickness of the first coating layer is 24 μm, the thickness of the second coating layer is 30 μm, and the total thickness of the negative electrode sheet is 114 μm;
[0136] The ratio of the depth of the groove on the outer surface of the negative electrode active material layer located in the single-sided area to the thickness of the negative electrode active material layer satisfies 0.33-0.5;
[0137] The mass content of silicon in the first negative electrode active material is 3%, and the mass content of silicon in the second negative electrode active material is 6%.
[0138] Example 3
[0139] The same method as in Example 1 is used, except that the negative electrode sheet is prepared in step (1), specifically as follows:
[0140] The first negative electrode active material (average particle size of 15 μm, specific surface area of 2.2 m 2 / g; including artificial graphite, hard carbon and silicon-carbon materials, wherein the mass ratio of artificial graphite, hard carbon and silicon-carbon materials is 87:3:10; the OI value of artificial graphite is 20, the specific capacity is 356mAh / g; the mass content of silicon in the silicon-carbon material is about 60%), styrene-butadiene rubber and conductive carbon black are mixed in a mass ratio of 95:3:2, deionized water is added to prepare a first coating slurry; the second negative electrode active material (average particle size of 20μm, specific surface area of 1.8m2 / g; including artificial graphite, hard carbon and silicon-carbon material, wherein the mass ratio of artificial graphite, hard carbon and silicon-carbon material is 81:4:15, the OI value of artificial graphite is 24, and the specific capacity is 358mAh / g; the mass content of silicon in the silicon-carbon material is about 60%, and the average particle size of hard carbon is 10μm), styrene-butadiene rubber and conductive carbon black are mixed evenly according to the mass ratio of 95:3:2, and deionized water is added to prepare a second coating slurry; the first coating slurry and the second coating slurry are coated on the surface of the carbon-coated copper foil by a transfer coater, and after drying and roller pressing, grooves are made on the surface (the depth h of the groove is 25μm, the width is 76μm, and the spacing is 1mm) to obtain a negative electrode sheet;
[0141] Wherein, the ratio L of the average particle size of the second negative electrode active material to the average particle size of the first negative electrode active material is 1.333; L×h is 33.3;
[0142] The porosity of the first coating layer is 24.1%, the porosity of the second coating layer is 34.3%, and the ratio of the porosity of the first coating layer to the porosity of the second coating layer is 0.7;
[0143] The surface density of the first coating is 7.24 mg / cm 2 The surface density of the second coating is 7.96 mg / cm 2 ;
[0144] The thickness of the first coating layer is 24 μm, the thickness of the second coating layer is 30 μm, and the total thickness of the negative electrode sheet is 114 μm;
[0145] The ratio of the depth of the groove on the outer surface of the negative electrode active material layer located in the single-sided area to the thickness of the negative electrode active material layer satisfies 0.33-0.5;
[0146] The mass content of silicon in the first negative electrode active material is 6%, and the mass content of silicon in the second negative electrode active material is 9%.
[0147] Example 4
[0148] The method is carried out in accordance with Example 2, except that the thickness of the first coating layer and the thickness of the second coating layer are regulated by changing the surface density of the first coating layer and the surface density of the second coating layer (the compaction density is controlled to remain unchanged), and the depth, width and spacing of the grooves are changed at the same time. Specifically:
[0149] The surface density of the first coating is 12.86 mg / cm 2 The surface density of the second coating is 13.01 mg / cm 2 ;
[0150] The thickness of the first coating layer is 42 μm, the thickness of the second coating layer is 57 μm, and the total thickness of the negative electrode sheet is 204 μm;
[0151] L×h is 85.2;
[0152] The depth h of the groove is 71 μm, the width is 117 μm, and the pitch is 1.8 mm.
[0153] Example 5
[0154] The method is carried out in accordance with Example 3, except that the thickness of the first coating layer and the thickness of the second coating layer are regulated by changing the surface density of the first coating layer and the surface density of the second coating layer (the compaction density is controlled to remain unchanged), and the depth, width and spacing of the grooves are changed at the same time. Specifically:
[0155] The surface density of the first coating is 12.86 mg / cm 2 The surface density of the second coating is 13.01 mg / cm 2 ;
[0156] The thickness of the first coating layer is 42 μm, the thickness of the second coating layer is 57 μm, and the total thickness of the negative electrode sheet is 204 μm;
[0157] L×h is 56;
[0158] The depth h of the groove is 42 μm, the width is 94 μm, and the pitch is 1.5 mm.
[0159] Example 6
[0160] The method is carried out in accordance with Example 2, except that the thickness of the first coating layer and the thickness of the second coating layer are regulated by changing the surface density of the first coating layer and the surface density of the second coating layer (the compaction density is controlled to remain unchanged), and the depth, width and spacing of the grooves are changed at the same time. Specifically:
[0161] The surface density of the first coating is 4.37 mg / cm 2 The surface density of the second coating is 5.62 mg / cm 2 ;
[0162] The thickness of the first coating layer is 14 μm, the thickness of the second coating layer is 22 μm, and the total thickness of the negative electrode sheet is 78 μm;
[0163] L×h is 26.4;
[0164] The depth h of the grooves is 22 μm, the width is 73 μm, and the pitch is 1 mm.
[0165] Example 7
[0166] The method is carried out in accordance with Example 3, except that the thickness of the first coating layer and the thickness of the second coating layer are regulated by changing the surface density of the first coating layer and the surface density of the second coating layer (the compaction density is controlled to remain unchanged), and the depth, width and spacing of the grooves are changed at the same time. Specifically:
[0167] The surface density of the first coating is 4.37 mg / cm 2 The surface density of the second coating is 5.62 mg / cm 2 ;
[0168] The thickness of the first coating layer is 14 μm, the thickness of the second coating layer is 22 μm, and the total thickness of the negative electrode sheet is 78 μm;
[0169] L×h is 16;
[0170] The depth h of the grooves is 12 μm, the width is 61 μm, and the pitch is 0.8 mm.
[0171] Example 8 Group
[0172] This group of embodiments is used to verify the impact of the change of "L×h".
[0173] This group of examples is carried out with reference to Example 5 and Example 7, except that L×h is adjusted by changing the depth h of the groove, as follows:
[0174] Example 8a is carried out in accordance with Example 5, except that the depth h of the groove is 11 μm, the width is 60 μm, the spacing is 0.8 mm, and L×h is 14.7;
[0175] Example 8b is carried out in accordance with Example 7, except that: the depth h of the groove is 72 μm, the width is 120 μm, the spacing is 1.8 mm, and L×h is 96 (this example only changes the depth of the groove located in the double-sided area, and the ratio of the depth of the groove located in the single-sided area to the thickness of the negative electrode active material layer still satisfies 0.33-0.5).
[0176] Example 9
[0177] This is used to verify the influence of the change in the “ratio L of the average particle size of the second negative electrode active material to the average particle size of the first negative electrode active material”.
[0178] The same method is carried out as in Example 1, except that L is regulated by changing the average particle size of the second negative electrode active material (and in order to minimize the change in L×h, the depth, width and spacing of the grooves are adjusted), as follows:
[0179] L is 2.353;
[0180] The average particle size of the second negative electrode active material is 20 μm and the specific surface area is 1.8 m 2 / g, and the OI value of artificial graphite is 24, and the specific capacity is 358mAh / g;
[0181] The porosity of the second coating layer is 34%, and the ratio of the porosity of the first coating layer to the porosity of the second coating layer is 0.6;
[0182] The depth h of the groove is 14 μm, the width is 63 μm, and the pitch is 0.8 mm.
[0183] Example 10
[0184] Used to verify the impact of the change that "the mass content of hard carbon in the second negative electrode active material is greater than the mass content of hard carbon in the first negative electrode active material".
[0185] The method is carried out in accordance with Example 1, except that the mass contents of artificial graphite, hard carbon and silicon-carbon material in the first negative electrode active material and the second negative electrode active material are changed as follows:
[0186] In the first negative electrode active material, the mass ratio of artificial graphite, hard carbon and silicon-carbon material is 92:6:2; in the second negative electrode active material, the mass ratio of artificial graphite and silicon-carbon material is 95:5.
[0187] Embodiment 11
[0188] Used to verify the impact of the change that "the mass content of silicon in the second negative electrode active material is greater than the mass content of silicon in the first negative electrode active material".
[0189] The method is carried out in accordance with Example 1, except that the mass contents of artificial graphite, hard carbon and silicon-carbon material in the first negative electrode active material and the second negative electrode active material are changed as follows:
[0190] In the first negative electrode active material, the mass ratio of artificial graphite to silicon-carbon material is 95:5; in the second negative electrode active material, the mass ratio of artificial graphite, hard carbon and silicon-carbon material is 92:6:2;
[0191] The mass content of silicon in the first negative electrode active material is 3%, and the mass content of silicon in the second negative electrode active material is 1.2%.
[0192] Example 12 Group
[0193] This group of embodiments is used to verify the influence of the change of the “recess type”.
[0194] This group of embodiments is carried out with reference to embodiments 1-3, except that the recess is changed from a groove to a hole, as follows:
[0195] Example 12a, according to Example 1, the hole depth h is 32 μm, the hole diameter is 98 μm, and the spacing is 200 μm;
[0196] Example 12b, carried out with reference to Example 2, the hole depth h is 42 μm, the hole diameter is 113 μm, and the spacing is 300 μm;
[0197] Example 12c was carried out with reference to Example 3, with the hole depth h being 26 μm, the hole diameter being 82 μm, and the spacing being 100 μm.
[0198] Example 13
[0199] Used to verify the impact of changing the "slot width".
[0200] The process is carried out in accordance with Example 1, except that the width of the groove is changed, specifically as follows: the width of the groove is 146 μm.
[0201] Embodiment 14
[0202] Used to verify the impact of changing the "slot spacing".
[0203] The process is carried out with reference to Example 1, except that the spacing between the grooves is changed, specifically as follows: the spacing between the grooves is 3 mm.
[0204] Example 15 Group
[0205] This group of examples is used to verify the influence of the change in the "ratio of the depth of the concave portion located in the single-sided area to the thickness of the negative electrode active material layer".
[0206] This group of examples is carried out with reference to Example 1, except that the ratio of the depth of the concave portion located in the single-sided area to the thickness of the negative electrode active material layer is adjusted by changing the depth of the concave portion located in the single-sided area, as follows:
[0207] In Example 15a, the ratio of the depth of the concave portion located in the single-side region to the thickness of the negative electrode active material layer is 0.24;
[0208] In Example 15b, the ratio of the depth of the concave portion located in the single-surface region to the thickness of the negative electrode active material layer is 0.8.
[0209] Example 16 Group
[0210] This group of embodiments is used to verify the influence of the change of the "depth h of the concave portion". In this group of embodiments, only the depth of the concave portion located in the double-sided area is changed, and the depth of the concave portion located in the single-sided area is not changed.
[0211] This group of examples is carried out with reference to Examples 5 and 6, except that h is changed, as follows:
[0212] Example 16a, carried out in accordance with Example 6, except that the groove depth h is 5 μm, the width is 23 μm, the spacing is 1.5 mm, and L×h is 6;
[0213] Example 16b is carried out in accordance with Example 5, except that the recess is changed from a groove to a hole (this is because the depth of the recess in Example 16a is the thickness of the electrode sheet, and if it is a groove, it will cause the negative electrode sheet to break) and h is changed (in addition, laser mode drilling is used in this example), the depth h of the hole is 204μm, the aperture is 94μm, the spacing is 1mm, and L×h is 272.
[0214] Example 17 Group
[0215] This group of examples is carried out with reference to Examples 16a and 16b, except that the average particle size of the first negative electrode active material and / or the second negative electrode active material is changed, as follows:
[0216] Example 17a is carried out in accordance with Example 16a, except that the average particle size of the second negative electrode active material is 10.5 μm, L is 1.05, and L×h is 5.25;
[0217] Example 17b is carried out in accordance with Example 16b, except that the average particle size of the first negative electrode active material is 10 μm, the average particle size of the second negative electrode active material is 20 μm, L is 2, and L×h is 408.
[0218] The embodiments 1-17 groups all meet the following requirements:
[0219] The tap density of the second coating is greater than the tap density of the first coating, and the tap density of the first coating is 0.6 g / cm 3 -0.85g / cm 3 The tap density of the second coating is 0.7 g / cm 3 -1g / cm 3 ;
[0220] The compaction density of the second coating is greater than that of the first coating, and the compaction density of the first coating is 1.4 g / cm 3 -1.8g / cm 3 The compaction density of the second coating is 1.5 g / cm 3 -2g / cm 3 ;
[0221] The particle size distribution of the silicon carbon material is Dv10 of 3μm-6μm, Dv50 of 6μm-12μm, and Dv90 of 12μm-25μm.
[0222] Test Case I
[0223] (1) Current collector elongation test
[0224] The elongation of the positive electrode current collector and the negative electrode current collector of the lithium ion secondary battery prepared in the embodiment in the first direction was tested, and the specific testing method was as follows:
[0225] The battery was placed at 25℃±2℃, left to stand for 5min, discharged at 0.2C to the lower limit voltage (3.0V), left to stand for 5min, charged at 0.7C to the upper limit voltage (4.53V), cut off at 0.025C, left to stand for 5min, discharged at 0.2C to the lower limit voltage (3.0V), left to stand for 5min, and cycled at 3.5C for 20 weeks; then the battery was disassembled, the positive and negative electrode sheets were taken out, the positive and negative electrode active material layers were peeled off, and the positive and negative electrode current collectors were obtained; or the positive and negative electrode current collectors in the empty foil area on the positive and negative electrode sheets were taken. According to the standard requirements, the positive and negative electrode current collectors were cut into 10mm long samples in the first direction (i.e., the direction perpendicular to the extension direction of the tabs).
[0226] 1. Clamp both ends of the specimen, make two marks in the center of the specimen, and measure the distance between the two marks as the length before stretching;
[0227] 2. Stretch the specimen, increase the strain by a small amount (0.2%-0.5%) each time, and record the stress each time; at the same time, observe and measure the change in the distance between the two marks;
[0228] 3. The distance between the two marks before the specimen breaks is taken as the length after stretching;
[0229] The elongation was calculated according to the following formula: Elongation = (length after stretching - length before stretching) / length before stretching x 100%. The results are recorded in Table 1.
[0230] (2) Current collector tensile strength test
[0231] The tensile strength of the positive electrode current collector and the negative electrode current collector of the lithium ion secondary battery prepared in the embodiment was tested, and the specific test method is as follows:
[0232] The battery was placed at 25℃±2℃, left to stand for 5min, discharged at 0.2C to the lower limit voltage (3.0V), left to stand for 5min, charged at 0.7C to the upper limit voltage (4.53V), cut off at 0.025C, left to stand for 5min, discharged at 0.2C to the lower limit voltage (3.0V), left to stand for 5min, and cycled at 3.5C for 20 weeks; then the battery was disassembled, the positive and negative electrodes were taken out, and the positive and negative current collectors in the empty foil area on the positive and negative electrodes were taken as samples. The tensile strength of the positive and negative electrodes was measured by the following method, as follows:
[0233] 1. Clamp the sample between the upper and lower clamps of the testing machine to ensure that it is firmly clamped;
[0234] 2. Start the testing machine and load slowly and evenly until the sample is broken. Record the load and strain data during the loading process. Calculate the tensile strength of the sample based on the recorded data and record the results in Table 1.
[0235] Table 1
[0236]
[0237] Note: “ / ” in Table 1 indicates no data. Since the ratio of the depth of the concave portion located in the single-sided area to the thickness of the negative electrode active material layer in Example 15b is relatively large, resulting in the breaking of the current collector, the elongation and tensile strength of the negative electrode current collector were not tested.
[0238] Comparative Example 1
[0239] The same method as in Example 1 is used, except that the negative electrode sheet is prepared in step (1), specifically as follows:
[0240] The negative electrode active material (average particle size of 9 μm, specific surface area of 3.4 m 2 / g; including artificial graphite, hard carbon and silicon-carbon materials, wherein the mass ratio of artificial graphite, hard carbon and silicon-carbon materials is 89:6:5, the OI value of artificial graphite is 12, and the specific capacity is 354mAh / g; the mass content of silicon in the silicon-carbon material is about 60%, and the average particle size of hard carbon is 10μm), styrene-butadiene rubber and conductive carbon black are mixed evenly in a mass ratio of 95:3:2, and deionized water is added to prepare a negative electrode active material slurry; the above-mentioned negative electrode active material slurry is coated on the surface of carbon-coated copper foil, and after drying and roller pressing, grooves are made on the surface (the depth h of the groove is 31μm, the width is 83μm, and the spacing is 1.2mm) to obtain a negative electrode sheet.
[0241] Comparative Example 2
[0242] The method is carried out in accordance with Example 1, except that the coating positions of the first coating slurry and the second coating slurry are swapped so that the first coating faces away from the negative electrode current collector and the second coating is located on the surface of the negative electrode current collector (the recess is still located on the surface of the negative electrode sheet).
[0243] Comparative Example 3
[0244] The method is carried out in accordance with Example 1, except that no hard carbon is added to the second negative electrode active material, that is, the second negative electrode active material is a mixture of artificial graphite and silicon-carbon material in a mass ratio of 95:5.
[0245] In some of the above embodiments and comparative examples, in order to regulate the average particle size of the first negative electrode active material and the average particle size of the second negative electrode active material while ensuring that the composition of each material in the first coating slurry and the second coating slurry remains unchanged, the average particle size of the artificial graphite and / or silicon-carbon material is adjusted. This adjustment is a routine operation in the field and will not be repeated in the embodiments.
[0246] Test Case II
[0247] (1) Energy density test
[0248] The batteries prepared in the examples and comparative examples were subjected to energy density tests, and the specific test methods are as follows:
[0249] The battery was charged at 0.7C to the upper limit voltage (4.3V), the cutoff current was 0.025C, and discharged at 0.5C to the lower limit voltage (2.5V). The discharge capacity and working voltage were output. The length, width and thickness of the battery were measured using a measuring instrument. The energy density was calculated using the formula: Energy density = discharge capacity × working voltage / (length × width × thickness). The results are recorded in Table 2.
[0250] (2) Fast charging performance test
[0251] The batteries prepared in the examples and comparative examples were tested for fast charging performance (3.5C and 4C). The specific test method for 3.5C is as follows:
[0252] Place the battery at 25℃±2℃, let it stand for 5min, discharge at 0.2C to the lower limit voltage (3.0V), let it stand for 5min, charge at 0.7C to the upper limit voltage (4.58V), cut off at 0.025C, let it stand for 5min, discharge at 0.2C to the lower limit voltage (3.0V) (do initial capacity test), let it stand for 5min, charge at 3.5C to 4.37V, charge at 2.8C to 4.37V, charge at 2C to 4.53V, charge at 1.5C to 4.58V, cut off at 0.05C; measure and record the data of the fully charged state, voltage and initial thickness; let it stand for 5min at 25℃±2℃, discharge at 0.7C to 3V, Standing for 5min, charging at 3.5C to 4.37V, charging at 2.8C to 4.37V, charging at 2C to 4.53V, charging at 1.5C to 4.58V, cutting off at 0.05C, standing for 5min, discharging at 0.7C to 3V, standing for 5min, cycling for 600 weeks, then measuring the voltage and thickness of the fully charged battery, disassembling the battery, and observing the lithium deposition on the surface of the negative electrode sheet; the capacity retention rate, thickness expansion rate and degree of lithium deposition are recorded in Table 2, thickness expansion rate = (full-charge thickness of the battery after 600 cycles - initial thickness) / initial thickness × 100%), the degree of lithium deposition is from light to heavy as follows: no lithium deposition, slight lithium deposition, lithium deposition and severe lithium deposition.
[0253] The specific test methods of 4C are as follows:
[0254] Place the battery at 25℃±2℃, let it stand for 5 minutes, discharge it at 0.2C to the lower limit voltage (3.0V), let it stand for 5 minutes, charge it at 0.7C to the upper limit voltage (4.58V), cut off at 0.025C, let it stand for 5 minutes, discharge it at 0.2C to the lower limit voltage (3.0V) (for initial capacity test), let it stand for 5 minutes, charge it at 4C to 4.37V, charge it at 3C to 4.37V, charge it at 2C to 4.53V, charge it at 1.5C to 4.58V, cut off at 0.05C; measure and record the fully charged state Data, voltage and initial thickness; stand at 25℃±2℃ for 5min, discharge 3V at 0.7C, stand for 5min, charge 4.37V at 4C, charge 4.37V at 3C, charge 4.53V at 2C, charge 4.58V at 1.5C, cut off at 0.05C, stand for 5min, discharge 3V at 0.7C, stand for 5min, cycle 600 weeks, then measure the voltage and thickness of the fully charged battery, disassemble the battery, and observe the lithium plating on the surface of the negative electrode; the capacity retention rate, thickness expansion rate and degree of lithium plating are recorded in Table 2.
[0255] Table 2
[0256]
[0257]
[0258] It can be seen from Table 2 that the battery prepared by the negative electrode sheet of the present invention has a higher energy density than that of the comparative example, and has a higher capacity retention rate, a lower thickness expansion rate and better lithium plating performance under high-rate charge and discharge conditions, indicating that the battery of the present invention can take into account both higher energy density and fast charging capability.
[0259] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector; the negative electrode active material layer comprises a first coating layer and a second coating layer stacked along the thickness direction of the negative electrode sheet, the first coating layer is close to the negative electrode current collector, and the second coating layer is away from the negative electrode current collector; the thickness of the negative electrode sheet is 30 μm-1000 μm; The first coating layer includes a first negative electrode active material, the second coating layer includes a second negative electrode active material; the second negative electrode active material includes a second graphite material and hard carbon; the ratio of the average particle size of the second negative electrode active material to the average particle size of the first negative electrode active material is L, 1 <L≤2.5; The negative electrode active material layer has a concave portion on its outer surface.
2. The negative electrode sheet according to claim 1, wherein: The depth of the concave portion is h, in μm; L and h satisfy: 6≤L×h≤300; Preferably, 14≤L×h≤100; More preferably, 16≤L×h≤86.
3. The negative electrode sheet according to claim 1 or 2, wherein: 1.05≤L≤1.4; and / or, h is 5-250, in μm; and / or, the average particle size of the first negative electrode active material is 5 μm-15 μm; and / or, the average particle size of the second negative electrode active material is 9 μm-24 μm; and / or, the average particle size of the hard carbon is 3 μm-20 μm; And / or, based on the total mass of the second negative electrode active material, the content of the hard carbon is 2%-10%.
4. The negative electrode sheet according to claim 1 or 2, wherein: The porosity of the second coating layer is greater than the porosity of the first coating layer; Preferably, the ratio of the porosity of the first coating layer to the porosity of the second coating layer is 0.5-0.98; more preferably 0.7-0.9; Preferably, the porosity of the second coating is 20%-50%; more preferably 25%-35%; Preferably, the porosity of the first coating layer is 10%-40%; more preferably 20%-25%.
5. The negative electrode sheet according to claim 1 or 2, wherein: The first negative electrode active material includes a first graphite material; the OI value of the second graphite material is greater than the OI value of the first graphite material; Preferably, the OI value of the first graphite material is 9-24; Preferably, the OI value of the second graphite material is 12-26.
6. The negative electrode sheet according to claim 1 or 2, wherein: The thickness of the negative electrode sheet is 70 μm-210 μm; and / or, the thickness of the first coating is 10 μm-80 μm; And / or, the thickness of the second coating layer is 20 μm-150 μm.
7. The negative electrode sheet according to claim 1 or 2, wherein: The recess comprises a hole and / or a groove; Preferably, the pore diameter is 40 μm-200 μm, and the spacing between the pores is 50 μm-1 mm; Preferably, the width of the groove is 20 μm-150 μm, and the spacing between the grooves is 200 μm-3 mm.
8. The negative electrode sheet according to claim 1 or 2, wherein: The depth h of the concave portion is 10-70, in μm; And / or, the negative electrode current collector has a region having the negative electrode active material layer on only one surface, and the ratio of the depth of the recessed portion on the outer surface of the negative electrode active material layer located in the region to the thickness of the negative electrode active material layer is 0.33-0.
5.
9. The negative electrode sheet according to claim 1 or 2, wherein: The first negative electrode active material includes at least one of hard carbon, soft carbon, mesophase carbon microspheres, soft carbon-coated graphite materials and hard carbon-coated graphite materials; the second negative electrode active material also includes at least one of soft carbon, mesophase carbon microspheres, soft carbon-coated graphite materials and hard carbon-coated graphite materials; Preferably, the mass content of hard carbon in the second negative electrode active material is greater than the mass content of hard carbon in the first negative electrode active material.
10. The negative electrode sheet according to claim 1 or 2, wherein: The first negative electrode active material and the second negative electrode active material each independently include a silicon-based material, and the silicon-based material includes at least one of elemental silicon, silicon-carbon material, silicon-oxygen material and silicon alloy; Preferably, the mass content of silicon in the second negative electrode active material is greater than the mass content of silicon in the first negative electrode active material; Preferably, the mass content of silicon in the first negative electrode active material is 1%-30%, and the mass content of silicon in the second negative electrode active material is 2%-50%; Preferably, the silicon-based material includes the silicon-carbon material, and the particle size distribution of the silicon-carbon material is as follows: Dv10 is 3 μm-6 μm, Dv50 is 6 μm-12 μm, and Dv90 is 12 μm-25 μm.
11. A lithium ion secondary battery, characterized in that: The lithium ion secondary battery comprises the negative electrode sheet according to any one of claims 1 to 10.
12. The lithium ion secondary battery according to claim 11, wherein The negative electrode current collector comprises a metal layer and a carbon coating layer located on at least one side of the metal layer, wherein the carbon coating layer comprises at least one of conductive carbon black, conductive graphite, carbon nanotubes and graphene; Preferably, after the lithium-ion secondary battery has been cycled for 20 weeks, the elongation of the negative electrode current collector in the first direction is 0.5%-15%; the cycle conditions are: at 25°C±2°C, stand for 5 minutes, discharge at 0.2C to 3.0V, stand for 5 minutes, charge at 0.7C to 4.53V, cut off at 0.025C, stand for 5 minutes, discharge at 0.2C to 3.0V, stand for 5 minutes, and cycle at 3.5C for 20 weeks; Preferably, after 20 cycles of the lithium-ion secondary battery, the tensile strength of the negative electrode collector is 200MPa-1000MPa; more preferably 300MPa-700MPa; the cycle conditions are: at 25℃±2℃, stand for 5min, discharge at 0.2C to 3.0V, stand for 5min, charge at 0.7C to 4.53V, cut off at 0.025C, stand for 5min, discharge at 0.2C to 3.0V, stand for 5min, and cycle at 3.5C for 20 weeks.
13. The lithium ion secondary battery according to claim 11 or 12, wherein: The lithium-ion secondary battery further comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode current collector, and the positive electrode current collector comprises aluminum foil and / or carbon-coated aluminum foil; Preferably, after 20 cycles of the lithium-ion secondary battery, the elongation of the positive electrode current collector in the first direction is 0.5%-5%; the cycle conditions are: at 25°C±2°C, stand for 5 minutes, discharge to 3.0V at 0.2C, stand for 5 minutes, charge to 4.53V at 0.7C, cut off at 0.025C, stand for 5 minutes, discharge to 3.0V at 0.2C, stand for 5 minutes, and cycle for 20 weeks at 3.5C; Preferably, after 20 cycles of the lithium-ion secondary battery, the tensile strength of the positive electrode collector is 100MPa-400MPa; more preferably 100MPa-250MPa; the cycle conditions are: at 25℃±2℃, stand for 5min, discharge at 0.2C to 3.0V, stand for 5min, charge at 0.7C to 4.53V, cut off at 0.025C, stand for 5min, discharge at 0.2C to 3.0V, stand for 5min, and cycle at 3.5C for 20 weeks.
Citation Information
Patent Citations
Composite negative plate and lithium ion battery
CN114156436A
Lithium ion battery
CN115377352A
Lithium ion battery
CN117239055A
Negative plate and lithium ion battery
CN117374219A
Battery
CN117728041A
Cited By
Negative plate, preparation method thereof and secondary battery comprising negative plate
CN120637387A
Secondary battery and electronic device
CN120978008A
Secondary battery and electronic device
CN120978008B
Negative electrode sheet and preparation method therefor, battery and electric device
WO2026065892A1